2014
DOI: 10.1108/cg-05-2012-0043
|View full text |Cite
|
Sign up to set email alerts
|

Impact of soft law regulation by corporate governance codes on firm valuation: the case of Germany

Abstract: Purpose – This paper aims to provide insight whether disclosed compliance with the German Corporate Governance Code (GCGC) leads to higher valuation on the German stock market. Design/methodology/approach – Based on agency theory, stakeholder theory and institutional theory, the authors conduct a meta-analysis and evaluate the value relevance of the compliance with the GCGC. Findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…Despite the growing diffusion of CGC and the intense academic debate about the effectiveness of these codes, empirical evidence on the impact of CGC is still far from definitive. In particular, research on the effect of CGC compliance on firm outcomes is inconclusive and further exploration is required (Stiglbauer and Velte, 2014). Some studies suggest that the fulfillment with CGC recommendations leads to better strategic decisions and therefore document a positive association between CGC compliance and different measures of firm performance, such as price-to-book ratio, Tobin's q, or profitability (Fernández-Rodríguez et al, 2004;Stiglbauer, 2010;Luo and Salterio, 2014;Rodríguez-Fernández, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the growing diffusion of CGC and the intense academic debate about the effectiveness of these codes, empirical evidence on the impact of CGC is still far from definitive. In particular, research on the effect of CGC compliance on firm outcomes is inconclusive and further exploration is required (Stiglbauer and Velte, 2014). Some studies suggest that the fulfillment with CGC recommendations leads to better strategic decisions and therefore document a positive association between CGC compliance and different measures of firm performance, such as price-to-book ratio, Tobin's q, or profitability (Fernández-Rodríguez et al, 2004;Stiglbauer, 2010;Luo and Salterio, 2014;Rodríguez-Fernández, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other authors have argued that CGC compliance can be used for ethical reasons to gain social legitimacy, which will improve investors' perceptions and lead to positive stock market reactions by improving firm value and share price development (Goncharov et al, 2006;Chavez and Silva, 2009;Kaspereit et al, 2015Kaspereit et al, , 2017, and corporate reputation (Hooghiemstra and van Ees, 2011;McCahery et al, 2016). Nevertheless, many studies fail to support the previous associations (Bassen et al, 2009;McKnight and Weir, 2009;Jain et al, 2011;Stiglbauer and Velte, 2014;Steger and Stiglbauer, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…With transparency, asymmetric agency cost was also expected to be reduced. Other researchers, such as Stiglbauer and Velte (2014), show that soft law regulations governing corporate governance have no impact on the value of firms. The effect of executive ownership on different economic variables has been assessed extensively in current literature (Iona et al ., 2017; Iona and Leonida, 2016; Ehikioya, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In a multiple jurisdiction investigation using a large sample of European companies in 2000 and 2001, Bauer, Günster, and Otten (2004) reported the surprising result that firm performance (ROE and Net Profit Margin) is negatively related with accomplishment of governance standards. Moreover, in a study of German companies listed at the Frankfurt Stock Market, Stiglbauer and Velte (2014) found that compliance with the local governance code is not a value driver. Conversely, Goncharov, Werner, and Zimmermann (2006), on another country study for Germany, found a positive significant relationship between their measure of compliance with a local governance code and stock market performance for large companies listed in DAX30 and MDAX.…”
Section: Background and Hypothesis Developmentmentioning
confidence: 99%